EFEKTIFITAS PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM PEMBELAJARAN BAHASA ARAB DI ERA SOCIETY 5.0: SYSTEMATIC LITERATURE REVIEW - Supriyanto, Supriyanto; Toifah, Nur (UIN Maulana Malik Ibrahim Malang, 2024)
This research aims to determine the effectiveness of using Artificial Intelligence (AI) in learning Arabic in the era of Society 5.0. The approach used is a concept analysis approach with the Systematic Literature Review (SLR) method, which consists of 8 stages, namely identification of research questions, developing research protocols, establishing database locations, selection of relevant studies, selecting quality studies, extraction of data from individual studies, synthesis of results, and presentation of results. Meanwhile, this research shows that the application of Artificial Intelligence (AI) in learning Arabic in the era of Society 5.0 is efficient and helpful in supporting the learning process. Among them, it can help in correcting errors in Arabic texts, helps search for material, references, questions, journals/articles, and digital books, it increases students' learning motivation because it is exciting and fun, supports language practice and understanding, helps practice speaking, writing, and gets instant grammar explanations, corrects their mistakes quickly and effectively, translates Arabic texts, helps in data analysis and understanding the context of Arabic texts, improves good use of the language, supports conversation practice, provides feedback and reference sources and learning tools with features that enrich the process of learning Arabic.